A comparative analysis of a-C:H by infrared spectroscopy and mass selected thermal effusion - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Applied Physics, 1998)
A comparative analysis of quantitative infrared absorption spectra and mass selected thermal effusion transients measured for a large number of hydrogenated amorphous carbon (a-C:H) films is presented in order to establish reliable IR absorption cross sections for the different hydrogen bonding configurations in the material. The structural character of the material and the hydrogen concentration were varied over a wide range from soft and wide band gap polymerlike a-C:H, via so-called diamondlike carbon, to the tetrahedral form of a-C:H deposited from a plasma beam source. The results show that the IR absorption cross sections from molecular hydrocarbons can well be transferred to the solid state as long as the material is of polymeric character, but that this procedure fails as soon as the material converts into a three-dimensional cross-linked and mechanically hard structure. For the latter material an empirical average IR absorption cross section for the C-H stretch band can nevertheless be determined from a comparison between hydrogen effusion and IR spectra. © 1998 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.1998.nat.dphy.IAP.exphys.acompa